Análise comparativa entre os retificadores monofásicos boost e SEPIC operando no modo de condução descontínuo - Pereira, Vanderson Damião (2016)
The work presents a comparative analysis among the experimental results, aiming power factor correction, efficiency and total harmonic distortion of the Boost and SEPIC single phase rectifiers. The rectifiers have high power factor, they are modulated by pulse-width and operate in discontinuous conduction mode. The results obtained in numerical simulation are presented in order to validate the theoretical study. In sequence the experimental results obtained in the three studied rectifier topologies are shown. The rectifiers are designed for the RMS input voltage of 127 V with 60 Hz frequency, rated power of 300 W, output voltage of 250 V and commutation frequency with 20 kHz.